Sodium chloride and water transport in the descending limb of Henle - Kokko, Juha P. (1970)
The unique membrane characteristics of the thin descending limb of Henle (DLH) play an integral part in the operation of the countercurrent system. We examined these properties in vitro by perfusing isolated thin descending limbs of rabbits. Active transport of NaCl was ruled out by failure to demonstrate either net transport or transmembrane potential difference when perfusing with isosmolal ultrafiltrate of the same rabbit serum as the bath. Transmembrane potential was zero, and net fluid transport was -0.07 ±0.06 nl mm(-1) min(-1), which also is not significantly different from zero. Passive permeability coefficient for Na(P(Na)) was determined from the disappearance rate of (22)Na from isosmolal perfusion solution. P(Na) was surprisingly low, 1.61 ±0.27 × 10(-5) cm sec(-1), a figure which is significantly less than P(Na) in the proximal convoluted tubule (PCT). Reflection coefficient for NaCl (σNaCl) was measured by perfusing the tubule with Na-free raffinose solution in a bath of rabbit serum to which sufficient NaCl was added to obtain conditions of zero net fluid movement. The measured σNaCl of 0.96 ±0.01 is significantly greater than σNaCl in the PCT. Water permeability to osmotic gradients (L(p)) was determined by perfusing with ultrafiltrate of rabbit serum in a bath made hyperosmotic by addition of either 100 mOsm raffinose or NaCl. L(p) with raffinose was 1.71 ±0.15 × 10(-4) ml cm(-2) sec(-1) atm(-1) and with NaCl 1.62 ±0.05 × 10(-4) ml cm(-2) sec(-1) atm(-1), indicating much greater water permeability than in the PCT. In each case the measured increase in osmolality of the collected fluid was primarily due to water efflux without significant influx of solute. The finding of low permeability to sodium and high permeability to water is consonant with the hypotheses that high interstitial concentration of Na in the medulla generates an effective osmotic pressure which results in concentration of the fluid as it courses through the DLH primarily by abstraction of water without significant net entry of NaCl.